(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The Second Amendment of the American Constitution arguably contains the formulation of the citizen’s right to a private ownership of guns. This amendment, however, has been the protagonist of interpretative battles that have reached the Supreme Court of the United States, and that continue today despite the decision of the Court. The issue of private gun ownership presents itself as a multifaceted interweaving of political, legislative, and social motivations, and is destined to increasingly become one of the factors that highlight the internal fracture of the American society. The essay explores the main elements related to the issue and its socio-political motivations, developments, and consequences.